Individual ability-based system design of dependable human-technology interaction - Jipp, Meike; Wagner, Achim; Badreddin, Essameddin (IFAC Proceedings Volumes, 2008)
This paper highlights the importance of considering especially individual differences in intelligence when designing systems and interfaces due to their impact on operator performance in new and unfamiliar situations. For this purpose, an approach is introduced which allows assessing performance-relevant abilities of the operators on the basis of their performance on everyday life tasks. In order to increase the overall human-machine system dependability, guidelines are derived about appropriate reconfigurations of the technical system and/or its interface on the basis of the assessed performance-relevant abilities. The impact of this new approach to dependable system and interface design is discussed.